The Effects of Sampling Lateralization on Bilateral Inferior Petrosal Sinus Sampling for Pediatric Cushing’s Disease—A Single Endocrinology Centre Experience and Review of the Literature - Moszczyńska, Elzbieta; Marczak, Elzbieta; Szalecki, Mieczysław; Kądziołka, Krzysztof; Roszkowski, Marcin; Zagata-Lesnicka, Patrycja (Frontiers in Endocrinology, 2021)
Background This study aims to analyze the diagnostic accuracy of bilateral inferior petrosal sinus sampling (BIPSS), the gold standard test for the differential diagnosis of ACTH-dependent Cushing’s syndrome (CS) in a group of pediatric patients with Cushing’s disease (CD). Methods This is a retrospective analysis which include 12 patients with hypercortisolemia and inconclusive pituitary MRI, who underwent bilateral inferior petrosal sinus sampling (BIPSS) and transsphenoidal surgery (TSS) from 2004 to 2020 in the Children’s Memorial Health Institute (CMHI) Warsaw, Poland. Pituitary origin of ACTH secretion was considered if baseline central to peripheral (C/P) ACTH level ratio was ≥ 2 or C/P ratio was ≥ 3 after human corticotropin-releasing hormone (hCRH) stimulation. The diagnosis was histologically confirmed in almost all cases after TSS. Results The diagnostic accuracy of BIPSS reached 75% at baseline and 83.3% after CRH stimulation. The compatibility of localization of a microadenoma by BIPSS with the surgical location was 66.7%. Conclusions Owing to its high diagnostic effectiveness, BIPSS remains the best test to differentiate CD from EAS. The indications for the procedure should be carefully considered, because EAS in the pediatric population, unlike in adults, is extremely rare. Moreover BIPSS has only limited value for indicating tumor localization.